Analisis Pengaruh Variasi Kecepatan Motor Induksi dan Jumlah Mata Pisau terhadap Kinerja Mesin Pencacah Botol Plastik - Rohman, Muhamad Nur; Hari Santoso, Rendy; Lestariningsih, Wiji (Virtual of Mechanical Engineering Article, 2025)
The aim of this research is to determine the effect of variations in motor rotation speed and the number of blades on plastic bottle chopping machines, in order to help human work in recycling plastic bottles by finding the highest level of machine effectiveness, because along with technological developments in the field of mechanical engineering, humans think about how how to make a tool that can provide convenience, comfort, environmentally friendly, and so on. This research method creates a plastic bottle chopping machine that works by cutting plastic bottles into small pieces, using a flat type AISI 420 Stainless Steel knife, and as a driver a single phase AC electric motor with a maximum speed of 1420rpm. The results of this research are regarding the effectiveness of production results from plastic bottle chopping machines. This discussion and testing aims to obtain the following data: 2 blades (800rpm=96kg/day), (1100rpm=172.8kg/day), (1420rpm=192kg/day). For 4 blades (800rpm=134kg/day), (1100rpm= 211.2kg/day), (1420rpm=2429.6kg/day). And 6 blades (800rpm=153.6kg/day), (1100rpm=230kg/day), (1420rpm=288kg/day). The results of this data and machine will certainly really help operators in increasing the effectiveness of plastic bottle chopping machines. Keywords: Blades Chopping, Machine Electric Motor, Plastic Bottle